(untitled) (Bangladesh Journal of Zoology, 2018)
A study was carried out on 60 cattle and 34 (56.66%) were found infested with ticks and lice. Mean parasitic burden was 2.26 ± 0.37 per square inches in cattle. Two species of arachnids, Haemaphysalis bispinosa (31.66%) and Rhipicephalus sanguineus (28.33%) lice, Linognathus vituli (23.33%) were identified. Mean parasitic burden was high in case of R. sanguineus (4.33 ± 0.48) followed by H. bispinosa (2.89 ± 0.62) and least in L. vituli (1.28 ± 0.16). Prevalence of ectoparasites were relatively higher in young animals aged > 1 - 3 year (66.66%) followed by in calf aged ± 1 year (50%) and lowest in adult aged > 3 year (44.44%) in cattle. The mean parasitic burden was higher in case of young (2.8±0.60) followed by adults (1.75 ± 0. 41) and calves (1.5 ± 0.34). Infestation was higher in female (64.10%) than the male (42.85%). Prevalence of ectoparasites were relatively higher in summer (75%) followed by in winter (55%) and lowest in rainy season (40%). The mean parasitic burden was highest in summer (1.93 ± 0.64) followed by in winter (1.72 ± 0.54) and lowest in rainy season (1.5 ± 0.50). Bangladesh J. Zool. 46(2): 137-145, 2018